The synthesis of hybridised tetramic acids for antibacterial activity - Lockett, J (2019)
Tetramic acids are a naturally occurring class of antibacterial compounds which have been widely assessed in the literature. Hybridised tetramic acids are those which contain the tetramic acid bonded to another antibacterially active compound with the aim of possessing dual-inhibition functionality. This thesis describes the synthesis and biological evaluation of hybridised tetramic acids. Chapter I reviews the methods by which drug discovery is employed in the search for novel antibiotics and the need for the discovery of antibiotics possessing novel modes of action. Previously employed tetramic acid syntheses and points of structural manipulation have been reviewed. A discussion of hybrids and a review of hybrids found in the literature has been produced. Chapter II discusses the synthesis of tetramic acids conjugated to other antibacterial compounds through various linkers. Tetramic acids were successfully conjugated with coumarins, imidazoles, and imidazolines and attempts at synthesising various other conjugates were made. Chapter II also discusses the structural features of the tetramic acids which were troublesome when attempted to purify the hybrid compounds. Chapter III investigates the synthesis of tetramic acid hybrids by fused hybridisation strategy. To achieve this, attempts were made at synthesising various spirocyclic tetramic acids however, isomerisation rendered the ability to characterise and biologically evaluate these compounds difficult. The synthesised compounds were evaluated for their antibacterial activity against multidrug resistant pathogens and disappointingly, all but one showed no antibacterial activity.